Mathematics Analogy Reasoning Ability of Junior High School Students in Solving Problems of Pyramid - Agusantia, Dwi; Nurlaelah, Elah (Universitas Wiralodra, 2023)
Mathematical analogy reasoning ability is a skill in drawing conclusions based on the similarities between the two things being compared. This study aims to describe students' mathematical analogy reasoning abilities on pyramid material in grade eight junior high school students. This research is qualitative with a case study approach. The subject of this study was grade eight at one of the junior high school students in the city of Bandung, totaling 20 students. The research instrument used in this study was essay test of the mathematical analogy reasoning abilities and has been tested for feasibility. The results of this study were that there was two students who mastered 4 indicators, 2 students mastered 3 indicators, 5 students mastered 2 indicators, 5 students mastered one indicator, and there were 6 students who did not master any of the indicators. Furthermore, 5 out of 20 students were able to identify source problems by looking for the characteristics or structure of the problem (Encoding), 13 out of 20 students were able to find relationships or solve source problems (Inferring), 3 out of 20 students were able to find the same relationship between source problem with target problem and build conclusions from the similarity of the relationship between problem one and question two (Mapping), 8 out of 20 students were able to select the correct answer and were able to explain the analogy or similarity used between the source problem and the problem targets (Applying).